2022
DOI: 10.1007/s11274-022-03439-6
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide produced by Lactiplantibacillus plantarum RO30 isolated from Romi cheese: characterization, antioxidant and burn healing activity

Abstract: Microbial exopolysaccharides (EPSs) extracted from lactic acid bacteria (LAB) are generally recognized as safe. They have earned popularity in recent years because of their exceptional biological features. Therefore, the present study main focus was to study EPS-production from probiotic LAB and to investigate their antioxidant and burn wound healing efficacy. Seventeen LAB were isolated from different food samples. All of them showed EPS-producing abilities ranging from 1.75 ± 0.05 to 4.32 ± 0.12 g/l. RO30 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…There is plenty of well-described evidence of the antioxidant activity of EPSs synthesised by Lactobacillus species, such as the EPSs produced by L. helveticus MB2–1, L. acidophilus P185, L. plantarum S123, L. plantarum RO30, L. plantarum MC5, L. casei NA-2, and L. pentosus . 23–29 Data obtained in this work showed the great antioxidant activity of many of the EPS crude extracts obtained from Lactiplantibacillus strains, especially LPG1.…”
Section: Resultsmentioning
confidence: 71%
“…There is plenty of well-described evidence of the antioxidant activity of EPSs synthesised by Lactobacillus species, such as the EPSs produced by L. helveticus MB2–1, L. acidophilus P185, L. plantarum S123, L. plantarum RO30, L. plantarum MC5, L. casei NA-2, and L. pentosus . 23–29 Data obtained in this work showed the great antioxidant activity of many of the EPS crude extracts obtained from Lactiplantibacillus strains, especially LPG1.…”
Section: Resultsmentioning
confidence: 71%
“…The scavenging abilities of P-EPS and C-EPS were 80.32 ± 1.67% and 88.12 ± 0.82% when the concentration reached 5.0 mg/mL. The study of Elmansy et al [45] showed that Lac. plantarum RO30 EPS had antioxidant activity when the EPS concentration reached 5 mg/mL; the ABTS radical clearance rate was 49.1% ± 1.32%.…”
Section: Metal-chelating Activity Of Hdc-08 Epsmentioning
confidence: 93%
“…The blood hemolytic activity of EPS producers was assessed by inoculating the isolates onto blood agar plates containing 5.0% sheep blood. After 24 h of incubation, the plates were checked for beta, alpha, or gamma hemolysis 24 .…”
Section: Methodsmentioning
confidence: 99%
“…The potent EPS producer with promising antimicrobial activity were tested for their probiotic tolerance properties against different acid and bile salts according to Nath et al 11 and Yadav et al 24 respectively.…”
Section: Methodsmentioning
confidence: 99%